Fluid balance during swim training - Butlion, Mornay Saul (My University, 2006)
During a typical swimming training session, the volume of fluid lost via sweat is not evident which may contribute to a swimmer not replacing fluid loss effectively. This study investigates fluid balance during a typical swim training session. The physiological responses measured included fluid loss, fluid gain and plasma lactate concentrations
A Research Report submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg in partial fulfilment for the degree of M.Sc.(Med)
Keywords: Water-Electrolyte Balance; Swimming; plasma; Lactate